Design And Implementation Of A Web-Based Financial Information System With Internal Audit Feature To Enchance Transparency And Accountability At Getsemani Church Sorong (Decode: Jurnal Pendidikan Teknologi Informasi, 2025)
The rapid development of information technology has transformed how organizations, including churches, manage financial data. This study presents a novel web-based church financial information system that integrates internal audit features to enhance transparency, accountability, and efficiency in fund management. Unlike traditional manual approaches using books and spreadsheets, the proposed system introduces a structured digital framework that facilitates accurate recording, timely reporting, and simplified audits. The system was developed using the Waterfall model and implemented with PHP, MySQL, and the Laravel framework in a web-based environment. It provides distinct user roles for treasurers, auditors, administrators, and congregants to ensure secure, role-based access and effective oversight. Validation through Black Box testing confirmed that all functional requirements were met. Usability testing using the System Usability Scale (SUS) with 20 respondents produced a SUS score of 84.6 (Excellent category), indicating high user satisfaction and ease of use. Performance testing conducted with Google Lighthouse under standard desktop conditions achieved an average score of 82.5, demonstrating good performance in terms of speed, accessibility, and technical optimization. Overall, the system has proven effective in improving the transparency, efficiency, and reliability of church financial management, thereby strengthening trust and governance within the digital transformation era.